2023
DOI: 10.3390/ijerph20031768
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Farmers’ Participation in Environmental Protection in the Context of Rural Revitalization: The Moderating Role of Policy Environment

Abstract: This study investigates the environmental protection behavior of farmers in the Guanzhong Plain region and the factors influencing their participation, in order to improve the enthusiasm of farmers’ participation and promote the formation of “good governance” in rural ecological environments. Based on interviews with 295 farmers, the influence of psychological cognitive factors on farmers’ intention and behavior to participate in environmental protection was analyzed using partial least squares structural equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The results of the effect of AC on PN supported hypothesis 2 and were consistent with the findings of 37,77,80,83 . According to these results, it can be concluded that awareness of the consequences of pro-environmental behaviors can affect people's normative commitment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of the effect of AC on PN supported hypothesis 2 and were consistent with the findings of 37,77,80,83 . According to these results, it can be concluded that awareness of the consequences of pro-environmental behaviors can affect people's normative commitment.…”
Section: Discussionsupporting
confidence: 88%
“…H7: Farmers' PBC toward pro-environmental behaviors have a significant impact on their intention.Merging NAM and TPB. NAM, rooted in pro-social behavioral intention and TPB based in self-interested motivation are widely adopted in the environmental psychology literature 64,76,77 , though there are specific advantages to applying the two models in tandem in order to improve responsiveness 47,64,65 , data depth 37,78,79 and hence to better explore the farmers' intention toward pro-environmental behaviors 47,80 . The principle advantage of a combined model is that it allows consideration of both pro-social and self-interested motivational factors in concert with one another 43,81 , and hence more rounded insights into pro-environmental behavioral context than their independent application 37,80,82,83 .…”
mentioning
confidence: 99%
“…The cow dung separate machine helps create a sense of environmental responsibility by minimizing impacts. from waste generated within their own cattle farm (Dong, H., et al, 2023;Egwutvongsa, S., et al, 2021). to strengthen farmers in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…The development of rural digital finance has promoted the establishment of rural environmental protection service platforms. Participation in environmental governance and other activities has effectively increased farmers' enthusiasm for engaging in environmental protection and has helped to improve their sense of social responsibility (Meng et al, 2022;Dong et al, 2023). Taking the "Ant Forest" in Alipay's personal carbon account platform as an example, users collect online energy and plant virtual trees to achieve real afforestation projects in reality, which attracts lots of subscribers to participate in environmental protection actions.…”
Section: Rural Digital Financementioning
confidence: 99%